A fluorogenic RNA aptamer nanodevice for the low background imaging of mRNA in living cells. Issue 9 (6th January 2022) - Xu, Tingting; Sun, Yao; Yu, Sha; Wu, Shaojun; Su, Yu; Tian, Ye; Zhou, Yuanzhen; Zhu, Jun-Jie
Abstract : A fluorogenic RNA aptamer nanodevice was developed that integrated NIR-light control and an entropy-driven RNA amplifier for the NIR-assisted imaging of low-abundance TK1 mRNA in living cells with a low background signal and high sensitivity. Abstract : A fluorogenic RNA aptamer nanodevice integrating an entropy-driven RNA amplifier with near-infrared (NIR) light control was developed, affording high contrast and sensitivity for imaging low-abundance mRNA in living cells. The design principle offers a new approach for developing low-background imaging systems for live-cell studies and manipulation.